COVID-19 and Community College Instructional Responses - Hart, Cassandra M.D.; Xu, Di; Hill, Michael; Alonso, Emily (Online Learning, 2021)
Like all educational institutions, community colleges rapidly shifted to online instruction in the wake of the COVID-19 pandemic. However, little is known about what factors shaped individual college responses. This survey of distance education leaders (N = 45) in the California community colleges system aimed to: a) characterize pre-COVID distance education resources, emergency responses to the pandemic, and readiness for online instruction in the fall, and b) determine how pre-COVID distance education resources, emergency responses, and fall readiness relate to each other. We find wide variability in pre-COVID distance education resources. These pre-existing resources were related to institutions’ responses: Colleges with fewer pre-COVID resources focused on foundational efforts such as creating online student services, while institutions with greater pre-COVID resources offered somewhat broader responses to training students and faculty in skills to successfully transition online. Finally, although colleges improved their readiness for continued remote instruction in the fall term in terms of training faculty and providing students with technology to access classes, respondents estimated that roughly a third of students would still face barriers accessing remote classes.